Digital health literacy among primary and secondary school teachers—a quantitative study - Rangnow, Pia; Fischer, Lisa; Hartmann, Anja; Renninger, Denise; Stauch, Lisa; Okan, Orkan; Dadaczynski, Kevin (Frontiers in Public Health, 2024)
Introduction Digital health literacy (DHL) is a key competency for individuals’ daily decisions toward their health behavior and wellbeing. While there is much focus on health literacy (HL) among the general population, teachers have been rarely addressed. Given the shortages in the teaching workforce in Europe and the impact of demanding working conditions on their health, it is important to address DHL in teachers. This paper examines the DHL of primary and secondary teachers and its associations with sociodemographic and school-related factors. Methods An online cross-sectional study was conducted with 1,600 German primary and secondary school teachers between October and December 2022. To assess DHL, the Digital Health Literacy Instrument (DHLI) including seven subscales was used. Statistical analyses were conducted on item and subscale level and an overall DHL score was calculated. Next to descriptive analyses, bivariate and regression analyses were conducted to explore potential associations with sociodemographic and school-related factors. Results The frequency of difficulty in using digital health information varied across DHL dimensions and was greatest for protecting privacy (70.9%) and evaluating reliability (40.0%). In multivariate analysis, females more often reported a sufficient ability of adding content (OR = 1.61, CI = 1.05–2.48), while males more often reported a sufficient ability to protect their privacy (OR = 0.45, CI = 0.27–0.75). Teachers with leadership positions more often reported a sufficient ability in adding content (OR = 1.78, CI = 1.07–2.98). Regarding the ability to determine the relevance of online health-related information, no associations with a predictor variable were found. Discussion The results suggest that it is important to examine the individual dimensions of DHL and their distinct associations with sociodemographic and school-level factors, rather than just to rely on the overall level of DHL. The differential patterns identified in this study suggest a greater intervention need for teachers from higher age groups, primary and secondary general schools, and those without leadership roles. However, based on the limited predictive power of the variables included, further individual and school-level factors and their potential association with DHL should be investigated in the future. The promotion of DHL should be integrated into both teacher education and in-service training.